Allyl‐2, 6‐dimethoxyphenol, a female‐biased compound, is robustly attractive to conspecific males of Bactrocera dorsalis at close range. Issue 9 (8th September 2019) - Shen, Jianmei; Hu, Liming; Zhou, Xinhua; Dai, Jianqing; Chen, Binghan; Li, Shufeng
Abstract: Insect cuticular hydrocarbons (CHCs) play important roles in mate recognition and chemical communication. To explore the cues regulating courtship and mating behaviour in the oriental fruit fly, Bactrocera dorsalis (Hendel) (Diptera: Tephritidae), CHCs were extracted from mature virgin female and male oriental fruit flies using n‐hexane. Nine compounds – i.e., 4‐allyl‐2, 6‐dimethoxyphenol (designated 'compound 3') and eight ester compounds – had significantly greater abundance in female samples than in males. Of these nine compounds, six (1, 2, 4, 5, 6, and 8) elicited electrophysiological responses from the antennae of male flies. Compound 3 did not elicit a detectable male antennal response, but in Y‐tube olfactometer bioassays, it exhibited robust attractiveness to conspecific males at close range. We speculate that compound 3 is a close‐range sex pheromone in B. dorsalis . A mating competition experiment revealed that compound 3 significantly increased the competitiveness of males, which implied that compound 3 might be used in control programs of B. dorsalis . Abstract : 4‐Allyl‐2, 6‐dimethoxyphenol, a female‐biased compound, did not elicit detectable electrophysiological responses from the antennae of male oriental fruit fly, Bactrocera dorsalis (Diptera: Tephritidae), but exhibited robust attractiveness to males at close range. This suggests that the compound, as a close‐range sex pheromone, plays an important role in courtship by physical contact. 4‐Allyl‐2, 6‐dimethoxyphenol improved the mating competitiveness of males, implying that it may be used in control programs of B. dorsalis .